Peran Tokoh Agama Mediasi Pertikaian Perkawinan - Lubis, Ahmad Rizal; Siregar, Syapar Alim (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is motivated by the role of religious leaders in resolving marital disputes in Sayurmatinggi Village. Religious figures are people who are prominent, respected and have a big role in the development of religious teachings, in this case Islam. The position of religious leaders who play an important role in society because they are considered as people who have a higher level and knowledge of religion compared to other members of the community. The problem in this study is about the role of religious leaders in mediating or efforts to reconcile the family or household of someone who is in a dispute that has the potential to lead to divorce is never done at all by religious leaders and even after the divorce then religious leaders play a role in it. This study aims to determine the role of religious leaders in mediating marital disputes in the Vegetable Sayurmatinggi community.This research was conducted directly in the field to obtain information and data as accurately as possible by using data collection techniques through interviews, observation and documentation. The objects in this study are the Village Head of Sayurmatinggi, traditional leaders, religious leaders, people in conflict.From the results of the research conducted, people are less aware of the role of religious leaders in the social order and religious leaders cannot play an active role in mediating marital disputes because a dispute in the household is a disgrace to the family itself while religious leaders are not part of the family. And the comments of the people in Sayurmatinggi village that it is more thick with custom in matters of marriage, on the grounds that culture and customs from ancient times have been applied in marriage matters, as well as statements by religious leaders although negative effects often follow later which can trigger various customary problems. prioritized in terms of marriage in Sayurmatinggi Village.